2021
DOI: 10.1002/osp4.482
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of pancreatic fat accumulation in Japanese type 2 diabetes patients treated with sodium‐glucose cotransporter 2 inhibitors: a retrospective study

Abstract: Background: Prior reports have suggested that pancreatic fat is related to type 2 diabetes. Sodium-glucose co-transporter-2 (SGLT-2) inhibitors are expected to reduce ectopic fat accumulation.Aim: This study assessed the effect of SGLT-2 inhibitors on pancreatic and liver fat accumulations in patients with type 2 diabetes. Materials and Methods:Retrospective analyses of indices of pancreatic and liver fat accumulations were conducted in 22 type 2 diabetes outpatients who were receiving SGLT-2 inhibitors for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Considering these reports, GLP-1RA, SGLT-2 inhibitors, and PPARα agonists might have the possibility that they also reduce pancreatic fat accumulation, resulting in the improvement of diabetic pathophysiology and pancreatic carcinogenesis. We enrolled 22 type 2 diabetic outpatients, who had undergone unenhanced abdominal CT examinations before and more than 3 months after SGLT-2 inhibitor administration, and investigated the changes of the degrees of liver and pancreatic fat accumulations [30]. As a result, no improvement in these fat accumulations was observed in total.…”
Section: Ectopic Fat In Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these reports, GLP-1RA, SGLT-2 inhibitors, and PPARα agonists might have the possibility that they also reduce pancreatic fat accumulation, resulting in the improvement of diabetic pathophysiology and pancreatic carcinogenesis. We enrolled 22 type 2 diabetic outpatients, who had undergone unenhanced abdominal CT examinations before and more than 3 months after SGLT-2 inhibitor administration, and investigated the changes of the degrees of liver and pancreatic fat accumulations [30]. As a result, no improvement in these fat accumulations was observed in total.…”
Section: Ectopic Fat In Pancreasmentioning
confidence: 99%
“…On the other hand, it has been reported that excess epicardial fat is involved in lipotoxicity due to supplying excess free fatty acids, cardiac hypertrophy, and cardiac diastolic dysfunction [31]. Epicardial fat is increased in patients with type 2 diabetes [30,31], and its accumulation has been reported to be associated with the presence of coronary artery disease [32,33].…”
Section: Ectopic Fat In Heartmentioning
confidence: 99%
“…Five (four prospective and one retrospective) clinical studies investigated changes in IPFD following the administration of SGLT-2 inhibitors in individuals with T2DM or prediabetes [ 42 46 ]. In addition to SGLT-2 inhibitors, individuals with T2DM received other glucose-lowering medications (including insulin in two studies [ 42 , 43 ]).…”
Section: Glucose-lowering Medicationsmentioning
confidence: 99%
“…Five (four prospective and one retrospective) clinical studies investigated changes in IPFD following the administration of SGLT-2 inhibitors in individuals with T2DM or prediabetes [ 42 46 ]. In addition to SGLT-2 inhibitors, individuals with T2DM received other glucose-lowering medications (including insulin in two studies [ 42 , 43 ]). The retrospective study identified 22 individuals in Japan over a 6-year study period and found no significant difference in IPFD (determined with the use of computed tomography) before and after administration of SGLT-2 inhibitors [ 42 ].…”
Section: Glucose-lowering Medicationsmentioning
confidence: 99%
See 1 more Smart Citation